Benefits of Black Seed According to Hadith - Fauzan Fadhillah; Naan Naan (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the meaning of Black Seed according to the hadith. This research is a qualitative type by applying literature study to interpret the hadith about Black Seed 'with a content analysis approach. The results and discussion of this study include the meaning of Black Seed